Α Numerical Analysis of Thermal and Shrinkage-Induced Warpage in Injection-Molded Polymer Parts - Nguyen, Tran-Phu; Le, Thanh-Long (Engineering, Technology & Applied Science Research, 2026)
Warpage is a common defect in injection-molded plastic parts, leading in dimensional inaccuracy and lower product quality, so it is crucial to recognize and control warpage. This study uses simulation-based analysis with Moldex3D, an advanced injection molding simulation software, to examine the main causes of warpage. The analysis focuses on two primary factors: the temperature and the shrinkage effect. The temperature effect arises from uneven cooling rates throughout the molded component, resulting in internal thermal tensions and geometric distortion. The shrinkage effect is related to material contraction during solidification and is influenced by flow direction, wall thickness, and material characteristics. This study uses simulation to assess the impact of various processing conditions and part geometries on overall warpage. The findings show that minimizing heat gradients and controlling shrinkage distribution are important for preventing warpage, optimizing processing parameters and enhancing the dimensional stability of injection-molded plastic products.